Perceptions of senior citizens on the use and desired features of a wristband for maintaining, strengthening, and regaining hand and finger function. Issue 1 (1st January 2020) - Weeks-Levy, Carolyn; Sadarangani, Gautam; Menon, Carlo
Abstract: The objective of this study was to understand whether seniors would wear a wristband technology to help them improve, retain, regain, or strengthen hand and finger function and to gather information about the desired features of the technology to enhance compliance in use. The strength and functioning of the hand and fingers decrease as people age and can have a detrimental impact on the individual's quality of life. Studies have shown that regular exercise of the hands can help the individual maintain hand strength and improve function. Two self-reported, online questionnaires were designed and administered to seniors. Of the 105 surveyed, 62% indicated they would wear a wristband. The top desired wristband features identified were ease of putting the device on, unobtrusiveness and comfort of the device with a desired price point of 99 or less. The majority of seniors surveyed were interested in wearing the wristband; however, results revealed that the wristband would need to be tailored for this population for use and uptake of the wristband. The results of this study provide insight into the features and functionalities of a wristband that would enhance user compliance in seniors who wished to improve hand and finger function.